2018
DOI: 10.1111/jfpp.13842
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet (UV‐C) radiation as a practical alternative to decontaminate thyme ( Thymus vulgaris L.)

Abstract: Alternative and cost‐effective decontamination methods for dehydrated herbs and spices are subject of interest in industry. In this work, a fluidized bed ultraviolet (UV‐C) system was tested for decontamination of dehydrated thyme. The samples were exposed to UV‐C radiation at 254 nm at 25.7, 51.4, 102.8, and 205.6 J/cm2 delivered at an intensity of 26.7 mW/cm2. UV‐C at 205.6 J/cm2 resulted in 1.8, 1.3, and 0.3 log cfu/g reductions in total aerobic mesophilic bacteria, total yeast/mold, and Bacillus cereus, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 35 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Ferriccioni et al [ 5 ] have indicated that dried thyme can be decontaminated before marketing and use by ultraviolet radiation treatment, which reduces the growth of aerobic mesophilic microorganisms, molds, and yeasts by more than 90%. Dogu-Baykut and Gunes [ 31 ] indicate that with this treatment, in addition to the microorganisms mentioned above, the development of B. cereus is also considerably reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Ferriccioni et al [ 5 ] have indicated that dried thyme can be decontaminated before marketing and use by ultraviolet radiation treatment, which reduces the growth of aerobic mesophilic microorganisms, molds, and yeasts by more than 90%. Dogu-Baykut and Gunes [ 31 ] indicate that with this treatment, in addition to the microorganisms mentioned above, the development of B. cereus is also considerably reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained have led to an increase in the shelf life of sardine fillets marinated and dried on the basis of Argan oil and thyme, this period was estimated at more than six (6) months unlike the product with argan oil, rosemary, and without marinade that will be destroyed in a few weeks. The findings result be explained by the antioxidant activity of thyme caused by phenolic monoterpenes, thymol, and carvacrol, which are the major compounds found in thyme (Dogu‐Baykut & Gunes, 2019; Nateqi & Mirghazanfari, 2018).…”
Section: Physicochemical Quality Controlmentioning
confidence: 99%